Formation of reading skills of students-inophones at the initial stage of learning the Russian language - Kibiryo Muzaffarovna Solijonova (Zien Journals, 2022)
The article describes the possibilities of using texts of historical content to improve the reading skills of students of foreign languages along with speech activity, phonetic, lexical, grammatical difficulties are shown, exercises for their prevention are recommended
Keywords: texts; difficulties; Russian as a foreign language; eaching reading as a type of speech activity